Subjectivity as "evidence": an exploration of medication adherence in the treatment of schizophrenia using in-depth interviews. Issue 2 (4th May 2019) - Ringwald, Whitney
ABSTRACT: Anti-psychotic medication is considered one of the most efficaciousinterventions for the treatment of severe schizophrenia, yet ratesof adherence are notoriously and consistently low despite volumesof medical research. Scientific knowledge has failed to improvemedication adherence because it systematically rejects subjectiveexperience in conceptualizing mental illness. In this paper, thecontent of interviews with people diagnosed with schizophreniareceiving Assertive Community Treatment are interpreted from aFoucaldian perspective to illuminate how disciplinary assumptionsperpetuate power inequities and may be a barrier to adequateresearch generation and effective treatments. Implications for futureresearch methodology and clinical approaches are discussed.